Evaluation of the isokinetic strength of hamstrings / quadriceps ratio in elite weight lifters - Liu, Y.-F.; Huang, C.-H.; Lin, S.-F. (Athens 2004: Pre-olympic Congress. Sport Science Through the Ages: Challenges in the New Millennium. 6.-11.11.2004, 2004)
Several studies have suggested the hamstrings and quadriceps (H/Q) ratio for the purposes of injury prevention and rehabilitation. However, only a few studies have considered the specific sport requirement for the muscle contraction speed. The purpose of this study was to evaluate the isokinetic strength of hamstrings and quadriceps (H/Q) ratio of elite weight lifters (WLs) and to investigate the difference of H/Q ratio in the dominant and nondominant side of the athletes. Methods Twenty national level WLs(13 males, 7 females) from NCPES volunteered as subjects. Two speeds of 60°/s and 300°/s was used to investigate subjects` isokinotic strength by Biodex System III dynamometer. Subjects performed 5 maximal voluntary knee extensions and flexions at both speeds, to test the peak torque of their strength. Results The results showed that the ratios were about 0.44-0.46 for women, and 0.51-0.53 for men at low and high speed(Table 1). There was no significant difference between the dominant and nondominant regards of gender(a <.05). Subjects consent form was obtained before the administrative from of the test. Discussion / Conclusions The results of this study suggested that weight lifters due to the specific movements required during squat down and up, making quadriceps strength stronger. Their H/Q ratios trended to have a specifical values. There was no significant of dominant and nondominant of athletes, thus, the concentric strength which was decided no matter what side could be accepted.